Psoralen and Isopsoralen Ameliorate Sex Hormone Deficiency-Induced Osteoporosis in Female and Male Mice. (30th April 2016) - Yuan, Xiaomei; Bi, Yanan; Yan, Zeman; Pu, Weiling; Li, Yuhong; Zhou, Kun
Abstract : Osteoporosis is a systemic skeletal disease, which is characterized by a systemic destruction of bone mass and microarchitecture. With life standard improved, the treatment of osteoporosis attracted more attention. The aim of this study is to verify the osteoprotective effect of psoralen and isopsoralen in females and males. Female and male mice were divided into 7 groups in this study: control group (sham-operation), model group (by ovariectomy or orchidectomy), positive control group (females given estradiol valerate; males given alendronate sodium), psoralen groups (10 mg/kg and 20 mg/kg), and isopsoralen groups (10 mg/kg and 20 mg/kg). After administration of psoralen and isopsoralen for 8 weeks, osteoporosis was ameliorated with increasing bone strength and improving trabecular bone microstructure as indicated by CT scan and pathology. Serum alkaline phosphatase (ALP), tartrate resistant acid phosphatase (TRACP), osteocalcin (OC), and C-terminal cross-linking telopeptides of type I collagen (CTX-1) were examined. Decreased TRACP and increased ALP/TRACP suggested restoring from bone destruction. These results suggest that psoralen and isopsoralen may be used as good natural compounds for the treatment of osteoporosis in males, as well as females.